A critical evaluation of biochemical markers for the diagnosis of acute pancreatitis: Biochemical markers in acute pancreatitis diagnosis - Alshahrani, Mohammed Merae (Cellular and Molecular Biology, 2025)
Acute pancreatitis (AP) is a common but poorly understood gastrointestinal illness. One explanation for this lack of awareness is the absence of clear recommendations on the use of biochemical markers to identify this illness. This is because knowledge in this field is always expanding. Serum amylase and lipase are two extensively utilized biochemical indicators in the diagnosis of AP. The lack of agreement on the optimal use of these markers, notably amylase and lipase, has an impact on diagnostic outcomes. Through a critical study of the current literatures, this review intends to explore in depth the use of biochemical markers in the diagnosis of AP. A comprehensive review of the literature had a glance at biochemical indicators in the context of AP diagnosis, diving into topics including pancreatic anatomy, functions, pathology, mechanisms of AP, etiologies, symptoms, and also diagnostic approaches. This review revealed areas of agreement and disagreement about biochemical indicators in the diagnosis of AP, as well as potential future research directions.